The Disliked Linguistic use of Imam Abu Ishaq Al-Shatibi (790 AH) in his Book, The Purifying Intentions - A Study in Terminology and Criteria - - Ghani , Mona; Falih, wafaa (Islamic Sciences Journal, 2023)
ABSTRACT This study determined the concept of hatred based on what was mentioned in the dictionaries and books of jurisprudence and language, because this venerable scholar has excelled in the sciences of syntax and the principles of jurisprudence, and this research highlights the criteria that al-Shatibi relied on in ruling that it is makrooh, with an approach between grammar and the principles of jurisprudence in that ruling. Hearing and correct analogy was not disliked for linguistic use, even if the Arabs did not utter it, then the consensus of linguists on the correctness of the issue defies it from the ruling of dislike.Note you missed transtation of many lines Measurement and gender differences.